Pengaruh Return On Equity, Debt To Asset Ratio, Earning Per Share, Total Asset Turnover dan Firm Size Terhadap Harga Saham Pada Peruahaan Manufaktur Sub Sektor Farmasi Yang Terdaftar Di Bursa Efek Indonesia Periode 2015-2019 - Islami Puji Lestari; Evaliati Amaniyah (Management Department of Economics and Business Of Trunojoyo Madura University, 2021)
This reaserch aims to determine the effect of Return On Equity, Debt to Asset Ratio, Earning Per Share, Total Asset Turnover and Firm Size to Stock Price inPharmaceutical Sub-Sector Manufacturing companies listed on the Indonesia Stock Exchange (BEI)2015-2019 period. This research was conducted in a descriptive quantitative manner using secondary data obtained on the Indonesia Stock Exchange. The population used in this study amounted to 10 Pharmaceutical Sub-Sector Manufacturing companies listed on the Indonesia Stock Exchange for the period2015-2019. The sampling technique used purposive sampling method and obtained 9 Pharmaceutical Sub-Sector Manufacturing companies that were used as samples. The data analysistechnique used is multiple linear regression. The results of data analysis, partially ROE has a significant positive effect on Stock Price, DAR partially has a significant effect on Stock Price, EPS partially has no significant negative effect on Stock Price, TATO has no significant positif effect on Stock Price, Partially Firm Size has no significant negative effect on Stock Price. Meanwhile, the results of the F test show that Return On Equity, Debt to Asset Ratio, Earning Per Share, Total Asset Turnover and Firm Size simultaneously have a significant effect on Stock Price.